THE EFFECT OF USING ECOPRINT LEAVES MEDIA ON THE LITERACY DEVELOPMENT OF CHILDREN AGED 4–5 YEARS - Saripah, Ipah; Purwani, Annisa; Fauziah, Nurul; Maulana, Khaidir; Bagus, Solihah; Rizal, Muhammad Fahmi; Ridwanulloh, M.S; Fijar Anugrah, Yuwan (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to determine the effect of Ecoprint Leaves media on the literacy development of children aged 4–5 years at TK Al-Adalah, Purwakarta Regency. The method used was a pre-experimental design with a one-group pretest–posttest approach. The research sample consisted of 20 children from Group A. The results showed a significant improvement in the children’s ability to recognize letters, copy, arrange words, and express their thoughts through symbols and drawings after the intervention. The Ecoprint media proved to be a concrete and enjoyable learning alternative for stimulating early literacy in young children. This medium also enhanced motivation, concentration, and creative exploration, which form the foundation of future literacy skills. The Ecoprint Leaves media was proven effective in improving early childhood language and literacy development because it is concrete, engaging, and provides multisensory learning experiences. It helps children more easily understand the concepts of letters and words and improves their storytelling and expressive skills through both drawing and writing.